2016
DOI: 10.1037/pst0000038
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a culturally informed therapy on self-conscious emotions and burden in caregivers of patients with schizophrenia: A randomized clinical trial.

Abstract: Objective Caring for a family member with schizophrenia often results in high degrees of self-conscious emotions (shame and guilt/self -blame), burden, and other serious mental health consequences. Research suggests that ethnic and cultural factors strongly influence the manner in which family members respond to mental illness. Research further indicates that certain cultural practices and values (spirituality, collectivism) may assist family members in coping with the self-conscious emotions and burden associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…In line with study hypotheses, patients assigned to the CIT-S condition had significantly less severe psychiatric symptoms at treatment termination than did patients assigned to the psychoeducation condition controlling for baseline symptoms (Weisman de Mamani et al 2014b). A later study using data from this project also indicated that CIT-S outperformed a psychoeducation only comparison condition in reducing caregiver burden (Weisman de Mamani & Suro 2015).…”
Section: Methodssupporting
confidence: 55%
See 2 more Smart Citations
“…In line with study hypotheses, patients assigned to the CIT-S condition had significantly less severe psychiatric symptoms at treatment termination than did patients assigned to the psychoeducation condition controlling for baseline symptoms (Weisman de Mamani et al 2014b). A later study using data from this project also indicated that CIT-S outperformed a psychoeducation only comparison condition in reducing caregiver burden (Weisman de Mamani & Suro 2015).…”
Section: Methodssupporting
confidence: 55%
“…). A later study using data from this project also indicated that CIT‐S outperformed a psychoeducation only comparison condition in reducing caregiver burden (Weisman de Mamani & Suro ).…”
Section: Methodsmentioning
confidence: 81%
See 1 more Smart Citation
“…Results from this intervention study demonstrated that when compared to a psychoeducation only control condition, patients assigned to the CIT-S condition had significantly lower psychiatric symptom severity at treatment termination (while controlling for baseline symptoms; Weisman de Mamani et al, 2014). Furthermore, caregivers in the CIT-S condition also demonstrated reduced levels of caregiver burden at treatment termination in comparison to those in the control condition (Weisman de Mamani & Suro, 2015). Patients without family members were invited to participate in a multifamily group version of the study which we are currently evaluating.…”
Section: Methodsmentioning
confidence: 99%
“…A vast body of literature has demonstrated that mental illness and drug addiction are physically, economically, and mentally damaging not only to the individuals who experience these disorders, but also their significant others (Orford et al, ; Weisman de Mamani & Suro, ; Wilkinson & McAndrew, ). These consequences are referred to in the literature as objective and subjective burdens (Biegel et al, ; Brady et al, ).…”
Section: Introductionmentioning
confidence: 99%